Steering the Metal Precursor Location in Pd/Zeotype Catalysts and Its Implications for Catalysis - Smulders, Luc C. J.; van de Minkelis, Johan H.; Meeldijk, Johannes D.; Tang, Min; Liutkova, Anna; Cheng, Kang; Roberts, S. Tegan; Sunley, Glenn J.; Hensen, Emiel J. M.; de Jongh, Petra E.; de Jong, Krijn P. (Chemistry an international journal, 2023)
Bifunctional catalysts containing a dehydrogenation–hydrogenation function and an acidic function are widely applied for the hydroconversion of hydrocarbon feedstocks obtained from both fossil and renewable resources. It is well known that the distance between the two functionalities is important for the performance of the catalyst. In this study, we show that the heat treatment of the catalyst precursor can be used to steer the location of the Pd precursor with respect to the acid sites in SAPO-11 and ZSM-22 zeotype materials when ions are exchanged with Pd(NH3)4(NO3)2. Two sets of catalysts were prepared based on composite materials of alumina with either SAPO-11 or ZSM-22. Pd was placed on/in the zeotype, followed by a calcination-reduction (CR) or direct reduction (DR) treatment. Furthermore, catalysts with Pd on the alumina binder were prepared. CR results in having more Pd nanoparticles inside the zeotype crystals, whereas DR yields more particles on the outer surface of the zeotype crystals as is confirmed using HAADF-STEM and XPS measurements. The catalytic performance in both n-heptane and n-hexadecane hydroconversion of the catalysts shows that having the Pd nanoparticles on the alumina binder is most beneficial for maximizing the isomer yields. Pd-on-zeotype catalysts prepared using the DR approach show intermediate performances, outperforming their Pd-in-zeotype counterparts that were prepared with the CR approach.